The shift to learning outcomes : policies and practices in Europe - (:unkn) unknown (Office for Official Publications of the European Communities, 2009)
"This study addresses the shift towards learning outcomes currently taking place in European education and training policies and practices. At European level, launching the European qualifications framework (EQF) and the European credit system for vocational education and training (ECVET) has put learning outcomes firmly on the political agenda. At national level the rapid development of national qualifications frameworks (NQF) points in the same direction. These developments have been captured in detail in this comparative study analysing the developments in the 32 countries taking part in the Education and training 2010 process. The study covers all the different subsectors of education and training - general, vocational and higher education - and is the first attempt to provide a complete overview of developments in this field. This wide coverage shows that the shift to learning outcomes can be seen as an integrated part of European and national lifelong learning strategies, addressing the need to create bridges between different parts of the education and training system." (Herausgeber, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2 Europa; Lernergebnisorientierung; Europäischer Qualifikationsrahmen; Europäisches Leistungspunktesystem; Nationaler Qualifikationsrahmen; Berufsbildungssystem; Reform; Europa